Importance of Candida Antigenic Factors: Structure-Driven Immunomodulation Properties of Synthetically Prepared Mannooligosaccharides in RAW264.7 Macrophages - Paulovičová, Ema; Paulovičová, Lucia; Farkaš, Pavol; Karelin, Alexander A.; Tsvetkov, Yury E.; Krylov, Vadim B.; Nifantiev, Nikolay E. (Frontiers in Cellular and Infection Microbiology, 2019)
The incidence and prevalence of serious fungal infections is rising, especially in immunosuppressed individuals. Moreover, co-administration of antibiotics and immunosuppressants has driven the emergence of new multidrug-resistant pathogens. The significant increase of multidrug-resistant pathogens, together with their ability to form biofilms, is associated with morbidity and mortality. Research on novel synthetically prepared immunomodulators as potential antifungal immunotherapeutics is of serious interest. Our study demonstrated the immunobiological activity of synthetically prepared biotinylated mannooligosaccharides mimicking Candida antigenic factors using RAW264.7 macrophages. Macrophage exposure to the set of eight structurally different mannooligosaccharides induced a release of Th1, Th2, Th17, and Treg cytokine signature patterns. The observed immune responses were tightly associated with structure, dose, exposure time, and selected signature cytokines. The viability/cytotoxicity of the mannooligosaccharide formulas was assessed based on cell proliferation. The structure-based immunomodulatory activity of the formulas was evaluated with respect to the length, branching and conformation of the various formulas. Glycoconjugate formulas with terminal β-mannosyl-units tended to be more potent in terms of Candida relevant cytokines IL-12 p70, IL-17, GM-CSF, IL-6, and TNFα induction and cell proliferation, and this tendency was associated with structural differences between the studied glycoconjugate formulas. The eight tested mannooligosaccharide conjugates can be considered potential in vitro immunomodulative agents suitable for in vitro Candida diagnostics or prospectively for subcellular anti-Candida vaccine design.